2021
DOI: 10.3389/fcvm.2021.650212
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lncRNA ENST00000609755.1 Confers Protection Against Early oxLDL-Induced Coronary Heart Disease

Abstract: Background: This study investigated the association between long non-coding RNAs (lncRNAs) and coronary heart disease (CHD) and further elucidated the potential biological roles of lncRNAs in CHD pathogenesis.Methods: A case-control study (590 patients and 590 controls) was conducted from February 2017 and March 2019 in Fuzhou, China. Environmental factors were investigated using questionnaires and physical examinations. Five representative lncRNAs were screened using lncRNA microarray (peripheral blood in 5 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Sun et al found that lnc-MICALL2-2 is up-regulated in CHD subjects. Knockdown lnc-MICALL2-2 subsequently confers protection against early pathological processes of oxidized low-density lipoprotein-induced CHD [ 10 ]. The level of lncRNA H19 is significantly decreased in the heart tissue of Sprague-Dawley rats undergoing MI surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al found that lnc-MICALL2-2 is up-regulated in CHD subjects. Knockdown lnc-MICALL2-2 subsequently confers protection against early pathological processes of oxidized low-density lipoprotein-induced CHD [ 10 ]. The level of lncRNA H19 is significantly decreased in the heart tissue of Sprague-Dawley rats undergoing MI surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to environmental and genetic factors, there is growing evidence that epigenetic changes may play a key role in the development of CHD. 8) Therefore, it has become a new challenge to further understand the pathogenesis of CHD and to search for markers for early diagnosis of CHD.…”
mentioning
confidence: 99%
“…11) Many of these lncRNAs play a role in pluripotency regulation and activation of heart-specific genes in particular and have been shown to be associated with CHD risk and AMI. 8) It has been reported that lncRNAs are present in the blood and may serve as diagnostic markers for cardiovascular diseases. 12) However, no specific lncRNA has been found that can be used to effectively identify early CHD.…”
mentioning
confidence: 99%